2008
DOI: 10.1074/jbc.m703021200
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase-activated Receptor-2 Induces Cyclooxygenase-2 Expression through β-Catenin and Cyclic AMP-response Element-binding Protein

Abstract: Chronic inflammation of mucosae is associated with an increased cancer risk. Tumorigenesis in these tissues is associated with the activity of some proteinases, cyclooxygenase-2 (COX-2), and ␤-catenin. Serine proteinases participate in both inflammation and tumorigenesis through the activation of proteinase-activated receptor-2 (PAR 2 ), which up-regulates COX-2 by an unknown mechanism. We sought to determine whether ␤-catenin participated in PAR 2 -induced COX-2 expression and through what cellular mechanism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 47 publications
5
34
0
Order By: Relevance
“…It has been demonstrated that activation of CREB downstream of ERK or p38MAPK might contribute to upregulation of COX-2 in certain cells including A549 cells (22,29,30). These reports are supported by our present findings that PAR2 stimulation actually induced phosphorylation of CREB in a manner dependent on the MEK / ERK pathway, but not the EGF receptor / p38MAPK pathway (see Fig.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…It has been demonstrated that activation of CREB downstream of ERK or p38MAPK might contribute to upregulation of COX-2 in certain cells including A549 cells (22,29,30). These reports are supported by our present findings that PAR2 stimulation actually induced phosphorylation of CREB in a manner dependent on the MEK / ERK pathway, but not the EGF receptor / p38MAPK pathway (see Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Unfortunately, in the present study, we could not obtain direct evidence showing that CREB is upstream of the PAR2-triggered COX-2 upregulation. However, Wang et al have reported that in A549 cells, the same cell line of ours, COX-2 upregulation caused by activation of PAR2 was suppressed by knockdown of CREB with the siRNA (22), supporting possible involvement of the MEK / ERK / CREB pathway in the PAR2-triggered COX-2 upregulation in A549 cells. Considering the blockade of COX-2 induction by an inhibitor of JNK (see Fig.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…PAR1 has also been implicated in cancer cell invasion and tumor progression (36,38,39). PAR2 functions to increase PG and cytokine levels in epithelial cells (33,40). In the current study, the fact that such dramatic lesion formation was observed at the site of ovarian removal where bleeding was present during and after uOVX suggests that tissue damage and bleeding may trigger an inflammatory reaction via PAR activation in this model.…”
Section: Discussionmentioning
confidence: 51%